2018
DOI: 10.1002/cyto.b.21747
|View full text |Cite
|
Sign up to set email alerts
|

Adult Bone Marrow Three‐Dimensional Phenotypic Landscape of B‐Cell Differentiation

Abstract: Background: The different B-cell subsets in human bone marrow result from a dynamic equilibrium between endogenous production, B-cell bone marrow reentry and terminal plasma cell differentiation. Our aim was to define and quantify the different medullary B-cell subsets.Methods: A series of 32 normal adult bone marrows plus 15 normal adult blood samples was studied by nine color flow cytometry (CD10, CD19, CD24, CD27, CD34, CD38, CD45, IgM, and IgD). With the Kaluza software radar plots, two 2D triple parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…In a recent report the B cell phenotypes in the BM have been assessed. Here, immature CD38 + B cells are described to represent one third of the B cells in the BM [13]. Adding other CD38-expressing cells such as transitional B cells provides comparable percentages as seen for CD27 - CD38 + B cells in our samples (42–44%).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In a recent report the B cell phenotypes in the BM have been assessed. Here, immature CD38 + B cells are described to represent one third of the B cells in the BM [13]. Adding other CD38-expressing cells such as transitional B cells provides comparable percentages as seen for CD27 - CD38 + B cells in our samples (42–44%).…”
Section: Resultssupporting
confidence: 59%
“…Adding other CD38-expressing cells such as transitional B cells provides comparable percentages as seen for CD27 - CD38 + B cells in our samples (42–44%). In the report, CD38 - B cells divide into CD27- and CD27 + B cells with the CD27 + being the less frequent subset [13]. Gating the two samples for CD27 + CD20 + conventional memory B cells showed frequencies of 7.24% (left femur) and 9.29% (right femur), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the blood and bone marrow, human memory B cells can be divided in three main populations: CD19 + CD27 + IgM + IgD + (similar to marginal zone (MZ) B cells), CD19 + CD27 + IgM + IgD − (IgM-ONLY) and class-switched CD19 + CD27 + IgM − (IgG + or IgA + ) (114, 115). An in-depth flow cytometry analysis of human bone marrow and blood samples showed that compared to the blood, the bone marrow was enriched in both MZ and switched B-cells (116). In the spleen, two main phenotypically distinct B cell populations exist and localize to separate areas of the lymphoid tissue.…”
Section: Lessons From Human Studiesmentioning
confidence: 99%
“…The review by Drs. Seegmiller, His and Craig, as well as the entire review series, are more fully described on the pages just following these by our two Guest Editors (9) Following the first review related to B-cell diagnostics, a greater understanding of how B-cells develop immunophenotypically is the inquiry behind the report by Carrion et al (10), a subject that has been touched upon in the journal's past pages (11,12). Using ninecolor flow cytometry, these investigators studied 32 normal adult bone marrows and 15 normal peripheral blood samples to define eight different B-cell stages in the bone marrow and five different stages in peripheral blood.…”
Section: Issue Highlightsmentioning
confidence: 99%